Pilot Study of a Novel First-Line Protocol (THOP) for Intermediate–Large B-Cell Lymphoma in Dogs - Alejandra Tellez Silva; Ester Yang; Marlie Nightengale; Nikolaos Dervisis; Shawna Klahn (Veterinary Sciences)
The current standard of care for treatment of intermediate–large B-cell lymphoma in dogs is a CHOP-based chemotherapy protocol. On-protocol disease progression is reported to be temporally associated with cyclophosphamide administration. The objectives of this prospective pilot clinical trial were to describe the adverse event profile and identify early signal of efficacy of a novel cyclophosphamide-free chemotherapy protocol consisting of temozolomide, doxorubicin, vincristine, and prednisone (THOP) as first-line treatment in dogs with diffuse large cell B-cell lymphoma. Treatment-naïve dogs with intermediate–large B-cell lymphoma were enrolled. THOP was administered as a three-week cycle for five cycles. Fourteen dogs were enrolled. All dogs achieved complete remission with a median time to progression (TTP) of 269 days and a median survival of 433 days. There were five grade III and four grade IV hematologic toxicities reported; one grade III gastrointestinal toxicity was observed. THOP appears to be well tolerated and an effective first-line protocol for the treatment of intermediate–large B-cell lymphoma in dogs.